Design and implementation of vibrational spectroscopy analysis - Weng, Zaishan (2013)
The spectroscopy technique is based on the Raman effect where the inelastic scattering of light due to energy exchanges between the incident photons and the vibrating molecules give rise to a spectrum of scattered light. This unique spectrum can be used to identify the substance being tested. [2nd Award]